Ethanolic extract of red dragon fruit inhibits growth of mosquito larvae - Dhina Ayu Susanti; Fitria Meliana Putri Milyunier; Galuh Maulidatin Nufus; Lita Aulia Pramesti; Nia Laela Nur Khamimi; Wima Anggitasari; Lindawati Setyaningrum; Inna Armandari (PAGEPress Publications, 2023)
Controlling the vector by eradicating mosquito larvae is frequently done by spreading Abate powder containing 1% Temephos as a larvicide agent. However, the use of Abate powder will possibly increase pesticide residue contamination in the water. This study aimed to explore the potential use of ethanolic extract from red dragon fruit skin to kill mosquito larvae. An experimental laboratory study was performed to examine the larvicidal activity of ethanolic extract from red dragon fruit skin. Maceration method was used to extract active compounds from the fruit skin. Subsequently, the viscous extract was formulated using the wet granulation method to obtain powder form. The larvicide test was done by comparing the lethal concentration (LC50) of mosquito larvae after treatment using the extract and the reference larvicide agent, 1% Temephos Abate. The treatment groups consisted of four different extract concentrations of 1%, 2%, 3%, and 4%. The LC50 of each treatment groups was then calculated against the negative control group. Phytochemical screening showed that the ethanol extract of red dragon fruit skin contains alkaloids, flavonoids, saponins, triterpenoids, and tannins. The larvicide test on Aedes aegypti mosquito larvae showed that the extract treatment hardly killed the Aedes aegypti mosquito larvae. However, on Culex mosquito larvae, the ethanolic extract of red dragon fruit skin was able to kill mosquito larvae, with LC50 value of of 19.06%. The ethanolic extract of red dragon fruit skin was effective on killing the Culex mosquito larvae but not the Aedes aegypti mosquito larvae.